2017
DOI: 10.1186/s13643-017-0547-y
|View full text |Cite
|
Sign up to set email alerts
|

Complications and health-related quality of life after robot-assisted versus open radical cystectomy: a systematic review and meta-analysis of four RCTs

Abstract: BackgroundRadical cystectomy is associated with high rates of perioperative morbidity. Robotic-assisted radical cystectomy (RARC) is widely used today despite limited evidence for clinical superiority. The aim of this review was to evaluate the effect of RARC compared to open radical cystectomy (ORC) on complications and secondary on length of stay, time back to work and health-related quality of life (HRQoL).MethodsThe databases PubMed, The Cochrane Library, Embase and CINAHL were searched. A systematic revie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 47 publications
0
22
0
Order By: Relevance
“…However, the study included in the meta-analysis was only one RCT and unpersuasive. Lauridsen et al 6 also conducted a meta-analysis that included four RCTs, but the results were not comprehensive and only included complications and health-related quality of life. Tang JQ et al 15 performed a meta-analysis that only focused on RARC versus ORC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the study included in the meta-analysis was only one RCT and unpersuasive. Lauridsen et al 6 also conducted a meta-analysis that included four RCTs, but the results were not comprehensive and only included complications and health-related quality of life. Tang JQ et al 15 performed a meta-analysis that only focused on RARC versus ORC.…”
Section: Discussionmentioning
confidence: 99%
“…4,5 Many studies have compared the advantages and disadvantages between MIRC (LRC or RARC) and ORC. [6][7][8][9][10][11][12][13][14][15] For example, Tang K et al 14 performed a meta-analysis and found that RARC seems to be a safer and less invasive treatment than ORC. Tang JQ et al 15 also performed a meta-analysis that suggested that RARC is a more minimally invasive treatment than ORC for BCa and has the advantage of reducing bleeding.…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, early randomized controlled trials failed to find any differences in complications at 90 days between RARC and ORC . As the last meta‐analysis on this subject was carried out in 2017, a significant body of novel data including both randomized (RCTs) and NRCTs have emerged, adding new evidence to the topic …”
Section: Introductionmentioning
confidence: 99%
“…In the subgroup of patients with ileal conduit, complication (grade III and IV) happened in more than half. Since it is known, that the highest number of life threatening complications is linked to urine leakage, with later intestinal complications due to urine contact with bowel anastomosis, in selected cases of very high load of the disease or poor general status, ureterocuntaneostomy has also to be taken into consideration, when deciding on the type of urine diversion [ 26 ]. It is also important, that most of the patients included into the study were in poor general condition.…”
Section: Disscussionmentioning
confidence: 99%